Book Review ~ The Costs of Open Learning: a handbook. Author: Thomas Hülsmann - Reviewed by Ricardo Vanella (International Review of Research in Open and Distributed Learning, 2003)
When I assumed the post as Director of the School of Distance Learning and Virtual Education in March 2000, my first task was to define a strategy to follow. In a context where trends indicated a dramatic increase in the application of new information and communication technologies used to support distance learning, there was a need for new institutional policies to provide a framework to support our activity. In short, I had to decide how to organize an academic unit to support distance learning. This task called for an analysis of all educational technologies available at the time, in order to develop the courses which were to be included in our educational offer. Costs were clearly an important consideration.By recalling this three-year-old experience, I am now in a position to assert that, as stated by Hilary Perraton in the Introduction, Thomas Hülsmann’s book is an effective tool for decision makers in the field of open and distance learning.